ASSESSMENT OF THE INTERNAL AND EXTERNAL ENVIRONMENT OF ENTERPRISES (Scientific electronic journal "Labor Economics and Human Capital", 2025)
In the process of globalization, any effective activity and action in the world must be formed based on the goals and means of developing a corporate strategy. To effectively manage this strategy, a deep analysis of the state of the internal and organizational environment and the implementation of possible risks are necessary. By analyzing the internal and external environment of the enterprise, it is possible to correctly distribute production resources, move to the stage of long-distance freight transportation, and further increase market share. It is known that the world has learned that the organization loses a lot of money annually due to the implementation of environmental analysis. The main purpose of the article is to give reasons why it is necessary to conduct an analysis of the internal and external environment, to introduce what is needed to do this, and to illustrate this topic with practical examples.
Keywords: External environment analysis, internal environment, Porter's five forces, strategic environment.